Analysis of the Influence of Regional Shopping, Human Development Index (HDI), Labor Force and Domestic Investment on District/City Economic Growth in Gorontalo Province - Afif Osamah Hermansyah; Muhammad Rusdi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of Regional Expenditures, Human Development Index (HDI), Labor Force and Domestic Investment on the Economic Growth of Districts/Cities in Gorontalo Province. The data used is secondary data, this research uses panel data which combines time series and cross section data. The research object consists of 6 districts/cities in Gorontalo Province for the 2017-2022 period. Then the data obtained was analyzed in this research using Eviews 12. The conclusion in this research is that there is a positive and significant influence between Regional Expenditures, Human Development Index (HDI), and Domestic Investment on Economic Growth, and there is no influence between the workforce on the economic growth of districts/cities in Gorontalo province in 2017-2022.